Homocysteine levels and its association with intraventricular hemorrhage in preterm infants born to preeclamptic mothers. (December 2013) - Kahramaner, Zelal; Sutcuoglu, Sumer; Cicek, Ebru; Erdemir, Aydin; Cosar, Hese; Turkoglu, Ebru; Colak, Ayfer; Ozer, Esra Arun
Abstract Objective: To investigate the relation between serum homocysteine levels and intraventricular hemorrhage (IVH) in preterm infants born to preeclamptic mothers. Method: This study included 84 preterm infants (42 born to preeclamptic mothers and 42 born to normotensive healthy mothers) who were admitted to Izmir Tepecik Training and Research Hospital Neonatology Clinic on the postnatal first day. The measurement of homocysteine levels in all samples were performed with an Immulite 2000 analyzer, using the chemiluminescence method. Cranial ultrasounds were performed on the fourth day and in the 1 month of age. Results: The mean plasma levels of homocysteine in infants born to preeclamptic mothers and in the control group were 8.2 ± 5.9 μmol/L and 5.3 ± 2.7 μmol/L, respectively. The plasma levels of homocysteine were significantly higher in the study group (p = 0.006). There was no association between the plasma homocysteine levels and IVH or other neonatal complications including necrotizing enterocolitis, retinopathy of prematurity, bronchopulmonary dysplasia and mortality. Conclusion: Our data suggest that plasma levels of homocysteine are higher among infants born to preeclamptic mothers, but these high levels are not associated with IVH and other neonatal complications in preterm infants.